Status Report on Selected Plan Projects/Sectors - Planning Commission (Planning Commission, 1981)
A quantitative analysis of production performance against targets and capacity during the third quarter of the year 1981-82(October-Decemberz1981) and against production in the corresponding period last year as well as the preceding quarter (July-September, 1981) is -given in Statements I, II and III. The analysis of project delays is furnished in Statement iv.
Monitoring Division, Planning Commission
Monitoring Division, Planning Commission